PRODUCTION AND CHARACTERIZATION OF POLYHYDROXYBUTYRATE (PHB) FROM LOCAL STRAIN OF HALOMONAS ELONGATA BK-AG25 AND ITS OPTIMIZATION THROUGH RECOMBINANT DNA TECHNOLOGY - Ode Sri Rizki, Wa
Economic progress and population growth unavoidably increase commodity and lifestyle changes, indirectly impacting plastic consumption and production. Currently, people regularly utilize petroleum-based plastics, which are difficult to decompose naturally, resulting in an accumulation of plastic waste in the environment. Plastic waste pollutes the environment and generates microplastic issues in organisms. New environment-friendly innovations are required to address this issue. Bioplastics are biopolymers that offer more environmentally favorable alternatives to petroleum-based plastics, reduce dependence on petroleum, and foster a circular economy. These materials can be utilized as a substrate for bioplastic production because they quickly break down into elements that support plant and microbial growth. Polyhydroxybutyrate (PHB) is a bioplastic produced by bacteria. PHB has several advantages over other types of bioplastics, especially its ease and speed of biodegradation when interacting with microorganisms in the environment. PHB has been increasingly popular in recent years due to its similar characteristics to petroleum-based plastics such as polypropylene. However, commercial production of PHB currently needs to be improved due to low production efficiency, high production costs, and complex downstream processes. This study aims to enhance the production of PHB from two local bacteria and to increase PHB production by employing recombinant DNA technology in Escherichia coli host cells through one plasmid and two plasmid systems. In this study, Nile red staining suggested that H. elongata BK-AG25 and Salinivibrio sp. can be used to produce PHBs. The structure of the produced PHB was analyzed using FT-IR. In a high medium (HM), both bacteria produced low levels of intracellular PHB, which was then enhanced using a single-factor method. After 72 hours of incubation, H. elongata BK-AG25 with 2.33±0.12 g/L biomass had the highest PHB content of 74±4% (w/w) in HM containing 0.2% (w/v) yeast extract and 5% (w/v) NaCl. Meanwhile, Salinivibrio sp. had 0.17±0.01 g/L biomass that produced the maximum PHB content of 63±6% (w/w) in the HM containing 15% (v/v) palm oil effluent (POME), 5% (w/v) NaCl, 0.1% (w/v) yeast extract, and 0.1% (w/v) ammonium sulfate. Under these conditions, H. elongata BK-AG25 and Salinivibrio sp. produced PHB 3.5 and 21.6 times more than standard HM, respectively. PHB produced by both bacteria has a sheet-like structure. PHB produced by H. elongata BK-AG25 was evaluated using 1H NMR. However, PHB generated by Salinivibrio sp. could not be assessed due to its low purity caused by using POME as a carbon source. The thermal stability analysis of PHB produced by H. elongata BK-AG25 revealed 91% decomposition at 263 °C, whereas PHB produced by Salinivibrio sp. decomposed only 74% at 285 °C. These findings support the low purity of PHB generated by Salinivibrio sp., despite the most effective purification technique. The presence of Na and Cl atoms in PHB produced by Salinivibrio sp. was revealed by atomic composition analysis using EDS, confirming the low purity of PHB from Salinivibrio sp. As a result, H. elongata BK-AG25 was chosen for further study to improve PHB production using recombinant DNA technology. The phbA, phbB, and phbC genes involved in PHB biosynthesis in H. elongata BK AG25 were successfully identified using a PCR approach. The sequences of these genes have been identified, and bioinformatics analysis has revealed that palindrome restriction enzyme sequences can be inserted at both ends of each gene to create expression operon systems on one plasmid (pET-phbABC) and two plasmids (pET-phbC/pET-phbAB). The phbA, phbB, and phbC genes in H. elongata BK-AG25 are 1211, 747, and 1813 bp, respectively. SDS-PAGE analysis revealed that the three genes in the one and two plasmid systems expressed identically, resulting in PhbA, PhbB, and PhbC proteins with sizes of 26, 43, and 68 kDa. After 48 hours of incubation in LB medium with 2% (w/v) glucose, recombinant E. coli BL21(DE3)/pET-phbABC produced 1.98±0.08 g/L biomass with the highest PHB content of 81±21% (w/w). After 72 hours of incubation, recombinant E. coli BL21(DE3)/pET-phbC/pET-phbAB produced 2.25±0.1 g/L of biomass, and the maximum PHB content was 86±0.5% (w/w). PHB produced by both systems has a sheet-shaped morphology, a high purity, and the same structure as H. elongata BK-AG25. The thermal stability analysis revealed that PHB produced by E. coli BL21(DE3)/pET-phbC/pET-phbAB is more thermally stable than by E. coli BL21(DE3)/pET-phbABC. These results show that a two plasmid system produces PHB at higher quantities and with higher thermal stability despite the longer incubation time. This is most likely due to more efficient expression of the phbC gene by an independent promoter in the two-plasmid system, allowing for optimum polymerization of PHB production. The findings of this study indicate that E. coli BL21(DE3)/pET-phbC/pET-phbAB is a viable recombinant clone for industrial-scale PHB production. However, the stability of both plasmids in host cells should continue to be investigated.